Fintech Achieving Sustainable Development: The Side Perspective of Crowdfunding Platform - Piliyanti, Indah (Shirkah: Journal of Economics and Business, 2018)
Crowdfunding has gradually been an emerging financing model of raising small amounts of money from a large number of people, mostly by means of optimizing certain website. The article proposes to explore the development of crowdfunding platform and the prospective of Islamic crowdfunding as the financial solution. The data has been gathered from certain website, under five standards: social network, event, user motivation, incentive versioning, and critical mass. The article reveals that along with other types of crowdfunding platforms, Islamic crowdfunding have disrupted sharia financing in Indonesia, yet the relate rule of financing have not accommodated this great development. Keywords: crowdfunding, Islamic crowdfunding, micro financing